Intermittent Ethanol Access Increases Sensitivity to Social Defeat Stress. (3rd February 2020) - Nennig, Sadie E.; Fulenwider, Hannah D.; Eskew, Jacob E.; Whiting, Kimberly E.; Cotton, Mallory R.; McGinty, Gabrielle E.; Solomon, Matthew G.; Schank, Jesse R.
Abstract : Background: Comorbidity between alcoholism and depression is extremely common. Recent evidence supports a relationship between alcohol exposure and stress sensitivity, an underlying factor in the development of depression. Our laboratory has recently shown that chronic alcohol gavage increases sensitivity to social defeat stress (SDS). However, the effects of voluntary alcohol consumption, resulting from protocols such as intermittent ethanol access (IEA), on defeat stress sensitivity have yet to be elucidated. Methods: We first assessed the effects of 4 weeks of IEA to 20% alcohol on sensitivity to subthreshold SDS exposure. Next, to examine neuroinflammatory mechanisms, we analyzed gene expression of inhibitor of NFkB (IkB) following IEA or chronic alcohol exposure (10 days of 3.0 g/kg alcohol via intragastric gavage). Then, we quantified NFkB activation via β‐galactosidase immunohistochemistry following IEA or chronic alcohol gavage in NFkB‐LacZ mice. Results: IEA‐exposed mice displayed an increase in sensitivity to subthreshold SDS compared to water‐drinking controls. We also found that IkB gene expression was decreased in the nucleus accumbens (NAC) and amygdala (AMY) following IEA but was not altered following chronic alcohol gavage. Finally, we observed increased NFkB activity in the central amygdala (CEA), basolateral amygdala (BLA), and medial amygdala (MEA) after IEA, and increased NFkB activity solely in the CEA following chronic alcohol gavage. Conclusions: These findings further corroborate that prior alcohol exposure, in this case intermittent voluntary consumption, can impact development of depressive‐like behavior by altering stress sensitivity. Furthermore, our results suggest the CEA as a potential mediator of alcohol's effects on stress sensitivity, as NFkB was activated in this region following both IEA and chronic alcohol gavage. Thus, this study provides novel insight on alterations in the NFkB pathway and identifies specific regions to target in future experiments assessing the functional role of NFkB in these processes. Abstract : We have previously shown that experimenter delivered alcohol gavage increases sensitivity to social defeat stress. Here, we demonstrate that voluntary alcohol intake using an intermittent access schedule also increases sensitivity to this stressor. We found that both alcohol gavage and intermittent access consumption increased the activity of the transcription factor NFkB in the central nucleus of the amygdala (CeA). Our results suggest the CeA as a neuroanatomical site of action for alcohol's effects on sensitivity to social stress.